"They Threatened to Call Immigration": Challenges Faced by Civil Protection Order Applicants and Respondents. (October 2022) - Bejinariu, Alexa; Troshynski, Emily I.
The current study seeks to better understand the challenges faced by immigrant applicants and respondents as they enter the civil court system for the purpose of obtaining protection orders. Structured observations of protection order hearings in a civil court are analyzed and include cases in which immigration-related issues were discussed. Through qualitative data analysis, three themes emerged. These include (1) threats of parental kidnapping and child abduction across country borders; (2) concerns over legal immigration documents; and (3) worries and/or threats of deportation. Findings suggest that battered immigrant victims have an acute vulnerability to experiencing multiple types of abuse. Implications for future research directions, policy recommendations, and strategies for improving the experiences of battered immigrants within the civil court system are also discussed.